Implementation of an Organizational Culture Based on Islamic Values ​​at the Manarul Quran El Yadah Islamic Boarding School, Bambu Apus - Nuriyatun Rizkiyah; Aep Saefullah (GURUPEDIA: Journal of Teacher and Education, 2026)
This study aims to explore the implementation of an organizational culture based on Islamic values ​​at the Manarul Quran El Yadah Islamic Boarding School in Bambu Apus. Islamic organizational culture is understood as a value system that not only shapes collective behavior but also fosters the spiritual and moral character of organizational members. This study uses a qualitative descriptive case study approach, with data collection techniques through in-depth interviews, participant observation, and documentation. The results show that values ​​such as trustworthiness, sincerity, discipline, and Islamic brotherhood have been embedded in various aspects of management and social interactions at the Islamic boarding school. The leadership of the kyai, who emphasizes exemplary behavior, deliberation, and honesty, is a key driving factor in maintaining this culture. Senior students are also empowered as agents of internalization of Islamic values ​​in the students' daily lives. Despite challenges such as inconsistent implementation of rules and a low understanding of spiritual values ​​as a whole, the organizational culture at this Islamic boarding school has been proven to support the formation of a religious, orderly, and character-building educational environment. This study recommends strengthening the strategy of internalizing values ​​in a sustainable manner to maintain the continuity of Islamic culture in modern Islamic boarding school educational institutions